9h+6=87

Simple and best practice solution for 9h+6=87 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9h+6=87 equation:


Simplifying
9h + 6 = 87

Reorder the terms:
6 + 9h = 87

Solving
6 + 9h = 87

Solving for variable 'h'.

Move all terms containing h to the left, all other terms to the right.

Add '-6' to each side of the equation.
6 + -6 + 9h = 87 + -6

Combine like terms: 6 + -6 = 0
0 + 9h = 87 + -6
9h = 87 + -6

Combine like terms: 87 + -6 = 81
9h = 81

Divide each side by '9'.
h = 9

Simplifying
h = 9

See similar equations:

| 7m+3=59 | | sin(2x+5)=sin(x-1) | | x^3-6x^2+20x=0 | | 2x^3-6x^2+20x=0 | | x+2.5z=18 | | 27x+11y+6z=1200 | | ln(x+7)=2 | | (60-d)(40-2d)=0 | | (60-d)(40-2d)=1312.5 | | 2a+4b+8c=200 | | x^3-2x^2-7x+6=0 | | 24(x+4)=24 | | 46(x-2)=18 | | 83(n+4)=7 | | 108(n-3)=12 | | (10+15)x(2+3)= | | 85n-6=19 | | 104y-3=14 | | (10)8-x+x=3[(10)x+8-x]-16 | | 2(-y+1)=5y+2(6-y) | | 3(x+2.98)=2x | | 123x+1=21 | | 13x+9y=136 | | 13+9y=136 | | 13x=9y+136 | | 164x+17=9 | | 2x^2-12x+y+14=0 | | -5600+200m=-2800 | | -5600+200m=0 | | 1.5n+(-2+0.5)=3-2(4.5+0.5) | | 4(x+3)=37 | | 5x+4(-3x+8)=x-8 |

Equations solver categories